Evaluasi Diri dan Manajemen Gudang Ditinjau dari Kinerja Karyawan PT. Zaindo Putra Logistik Banjarmasin - Mardiana Mardiana; Kamsariaty Kamsariaty; Harmuzan Harmuzan; Nur Achmad Jabrial (Jurnal Pendidikan Manajemen Transportasi, 2023)
The research method used is descriptive qualitative research. Data processing techniques include observation, interviews, documentation and literature. Based on the population and informants, 10 respondents were obtained. The conclusions in this research include assessing self-evaluation and performance of warehouse employees, which is the activity of managers or superiors to evaluate employee work performance behavior and determine subsequent policies. Performance assessment is included in human resources, comparative human resources are the key to the company's success. By conducting performance assessments on employees, employees will always try to do the maximum possible in every activity provided by the company or leaders and managers, and it will also be easy for them to carry out company activities in the field of increasing employee positions or seeing employee performance that is not optimal. Apart from that, another aim of the company's self-evaluation and performance assessment of warehouse employees is the company's efforts to provide human resource development to improve the performance and competence of the employees concerned. Performance appraisal is not a punishment but a form of leadership attention towards employees.